The complete chloroplast genome of Pimpinella rhomboidea var. tenuiloba - Jinbo Tan; Yan Yu (Mitochondrial DNA. Part B. Resources, 2018)
Pimpinella rhomboidea var. tenuiloba is an endemic species in China. The complete chloroplast genome sequence of P. rhomboidea var. tenuiloba was generated by de novo assembly using whole genome next generation sequencing. The genome was 146,655 bp in length, composed of four distinct regions such as large single copy (LSC) region of 94,684 bp, small single copy (SSC) region 17,537 bp and a pair of inverted repeat regions of 17,217 bp. The genome annotation predicted a total of 113 genes, including 80 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. Phylogenetic analysis with the reported chloroplast genomes revealed that P. rhomboidea var. tenuiloba has close relationship with genus Angelica.